TANGGUNG JAWAB PERDATA PEMALSUAN IDENTITAS GENDER PADA ATLET VOLI (ANALISIS PASAL 1365 KUHPERDATA) - Khoirun Nisak; Ika Ayudyanti; Abdul Basid (Cattleya Darmaya Fortuna, 2026)
This study analyzes the polemics of gender identity discrepancy among volleyball athletes from the perspective of Indonesian civil law, focusing primarily on the implementation of Article 1365 of the Indonesian Civil Code (KUHPerdata). Employing a normative legal research method with a statutory and case-based approach, this study examines the qualification of identity inconsistency as a Tort (Perbuatan Melawan Hukum) that infringes upon the subjective rights of the federation and the principle of fairness in competition. The results indicate that an athlete's civil liability is predicated on the cumulative fulfillment of the elements of tort: fault (opzet or culpa), material damages (damnum emergens and lucrum cessans) and immaterial damages (reputational degradation), and a causal relationship satisfying the conditio sine qua non parameter. The implications of applying this norm introduce an extra-contractual restorative obligation for the perpetrator to perform restitutio in integrum, including the restitution of economic benefits (unjust enrichment). To mitigate systemic risks, this research recommends accelerating regulatory reform through amendments to the National Sports Law to mandate compulsory biometric verification and interoperable integration of civil registry databases. Furthermore, the establishment of a federation guarantee fund and the formulation of specific sports-related loss valuation guidelines are proposed as legal protection instruments to maintain the integrity and dignity of the national sports ecosystem sustainably.